Penguatan Upgrade Diri Berbasis Pengetahuan Digitalisasi dan Komunikasi Bisnis untuk MPPO-UMKM Kendal - Dewi, Idah Kusuma; Satato, Yuniarto Rahmad; Maryani, Tri; Samtono, Samtono (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Community service activities for MPPO-UMKM Kendal aim to provide motivation and knowledge so that members of the community become stronger in the future by helping to identify self-quality, seize opportunities, manage, improve business skills, and similar aspects that allow for the reduction or resolution of common problems faced by MPPO-UMKM Kendal. And increasing awareness of MPPO-UMKM Kendal members about the development of their business so that it has a more important meaning as the main actor in the business world. The activity method is in the form of counseling using a lecture model and interactive discussion with MPPO-UMKM Kendal members. The results of the activity are in the form of increasing participant understanding of the importance of motivation to upgrade themselves through knowledge about digitalization and the need for proper communication in marketing their products. This will be followed up with the next activity because this community service is the first part of a series of community service activities for the MPPO-UMKM Kendal community.